E-Government and Bureaucratic Corruption in Nigeria: Successes and Challenges - Abdulkareem, Abdulrazaq Kayode; Ishola, Abdulrasaq Ajadi; Abdulkareem, Zulpha Jumoke (Universitas Muhammadiyah Yogyakarta, 2021)
This paper explored the successes and challenges of Information and Communications Technology (ICT) adoption in the combat against bureaucratic corruption in the Nigerian public service. This study adopted a qualitative approach via in-depth interviews for data collection and thematic analysis. Interviews were conducted within purposively sampled public officials with over ten years of experience in the public service. Two major themes were identified; successes and challenges encountered in the fight against bureaucratic corruption with the use of ICT. It is discovered in this paper that ICT has played a significant role in the combat against bureaucratic corruption by increasing the revenue of the government through the Integrated Personnel Payroll Information System (IPPIS) and Treasury Single Account (TSA) systems. However, challenges faced in this regard can be attributed to infrastructural gap, shortage of ICT skilled personnel and resistance by the public officials. It is therefore recommended that for the little success to be sustainable, those challenges must be mitigated.